Frequency of Retinopathy in Newly Diagnosed Type 2 Diabetes Mellitus - Muhammad Usman, Gohar Khan, Ahmad Ali Wassan, Amina Zulfiqar, Hafiz Muhammad Jahan Zaib (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to find out how common retinopathy is in newly diagnosed patients with type 2 diabetes. Methods: This cross-sectional research included 100 newly diagnosed patients with type 2 diabetes patients who attended the diabetic health center at Federal Govt. Polyclinic, postgraduate medical institute, Islamabad from 1st March 2022 to 31st July 2022. The research precluded those who had type-1 diabetes, high blood pressure, retinal artery obstruction, retinal venous obstruction, renal glomerulonephritis, or hemoglobinopathies retinopathy. Following pupillary dilation with Mydriacyl, a comprehensive fundoscopic examination had been performed, and retinopathy was classified as Mild to Moderate non proliferative (mild to moderate NPDR), severe non proliferative (severe NPDR), or proliferative (PDR). Results: The respondents’ average age had been 47 years, with 65% men and 35% women. At the onset of the disease, 9% of patients had been diagnosed to have retinopathy. The demographic and clinical characteristics of newly diagnosed diabetes mellitus patients are shown in Table. In the univariate analysis, there was a statistically significant difference between the characteristics of patients who had retinopathy compared to those who did not have it. Patients with retinopathy were older in age, had a higher prevalence of smoking and alcohol consumption, and had much higher levels of fasting blood sugar, HbA1c, cholesterol, triglycerides, LDL, BMI and serum creatinine, compared to patients with no retinopathy (Table). The prevalence of retinopathy was much higher in the categories of patients with higher levels of HbA1c and BMI, compared to those with lower levels. Practical implication: The prevalence of retinopathy in newly diagnosed type 2 diabetes mellitus patients was found to be relatively high in this study. This underlines the importance of detailed ophthalmic examination of all patients at the time of diagnosis Conclusion: The said research reveals a greater incidence of retinopathy in recently diagnosed people with type 2 diabetes. This highlights the significance of performing a thorough ophthalmic examination on all diabetic individuals at the time of assessment. Keywords: Diabetes Mellitus. , Retinopathy, And Retinal Hemorrhages, Fundoscopic, Prevalent,